2019
DOI: 10.21273/hortsci13787-18
|View full text |Cite
|
Sign up to set email alerts
|

Germination of Persian Walnut Somatic Embryos and Evaluation of their Genetic Stability by ISSR Fingerprinting and Flow Cytometry

Abstract: Somatic embryos (SEs) can play important roles in genetic manipulation and breeding. They can be used as targets for induced mutagenesis, as material for cryopreservation and germplasm conservation, and for transformation or gene editing in support of plant improvement and proof of gene function. However, germination rates of walnut (Juglans regia) SEs are low, and the genetic stability of plantlets regenerated from them has not been explored. Here, we studied first the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…In the present investigation, no major differences between fluorescence peak derived from nuclei of Ruta chalepensis plantlets and ex vitro plants were found. The findings of flow cytometric analysis are consistent with those obtained from earlier research on Mentha arvensis [69], Puya berteroniana [112], Solanum lycopersicum [113], Cucumis melo [114], Bacopa monnieri [34], Curcuma zedoaria [72], and Juglans regia [115].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present investigation, no major differences between fluorescence peak derived from nuclei of Ruta chalepensis plantlets and ex vitro plants were found. The findings of flow cytometric analysis are consistent with those obtained from earlier research on Mentha arvensis [69], Puya berteroniana [112], Solanum lycopersicum [113], Cucumis melo [114], Bacopa monnieri [34], Curcuma zedoaria [72], and Juglans regia [115].…”
Section: Discussionsupporting
confidence: 90%
“…It has been shown that the use of RAPD and DAMD molecular markers is efficient in determining the genetic stability of regenerated plants in a variety of medicinal plant species, including Withania somnifera [108], Henckelia incana [109], Avicennia marina [110], Ruta graveolens [18], Curcuma zedoaria [72], Artemisia vulgaris [100], Anarrhinum pubescens [111], and Anthurium andraeanum [106]. In recent years, it has been shown that a flow cytometry-based approach for evaluating in vitro raised plantlets is an excellent technique for assessing the clonal integrity and ploidy status in micropropagated plants [34,71,72,112,113]. In the present investigation, no major differences between fluorescence peak derived from nuclei of Ruta chalepensis plantlets and ex vitro plants were found.…”
Section: Discussionmentioning
confidence: 99%
“…Stability in genome size has also been reported in plants regenerated by somatic embryogenesis of Coriandrum sativum [ 88 ], Hibiscus sabdariffa [ 89 ], Milkweed spp. [ 90 ], Juglans directed [ 91 ], and Rauvolfia serpentina [ 92 ] evaluated by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…Flow cytometry has been used to assess plant ploidy [ 57 ]. In this research, flow cytometry is used to identify ploidy in all parental and F 1 hybrid combinations [ 58 ].…”
Section: Methodsmentioning
confidence: 99%